Islam Politik dalam Politik Global:Sebuah agenda penelitian dalam Studi Hubungan Internasional - Wicaksono, Arief (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
Islam and modernity has been encountering each other for such a long time since the colonialism period to the contemporary situation of global politics in the post of September 11th 2001. The result of such encounter varies, depending upon the complexity of the changeably deteriorating situation of Muslims themselves. The development of political Islam is not alien to the context of international relation. The contemporary model of Islamic renaissance should consider the development of global interconnection in one hand, and the escalation of anti-Islam and anti-immigrant sentiments in the West on the other.